2012
DOI: 10.1063/1.4768726
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of CuCrO2 thin films grown on Al2O3(001) by oxygen plasma assisted molecular beam epitaxy

Abstract: Electronic structure of CuCrO2 thin films grown on Al2O3(001) by oxygen plasma assisted molecular beam epitaxy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 45 publications
7
31
1
Order By: Relevance
“…This absorption is in line with the previously reported studies on the delafossite CuCrO 2 phase. 37,39,72,73 However, another steep increase of the absorption is noticed at 2.5 eV for x Z 0.66. This absorption edge at 2.5 eV is particularly steep for the Cu 2 O reference coating (w = 1).…”
Section: Optical Propertiesmentioning
confidence: 97%
“…This absorption is in line with the previously reported studies on the delafossite CuCrO 2 phase. 37,39,72,73 However, another steep increase of the absorption is noticed at 2.5 eV for x Z 0.66. This absorption edge at 2.5 eV is particularly steep for the Cu 2 O reference coating (w = 1).…”
Section: Optical Propertiesmentioning
confidence: 97%
“…36 There are many methods available for the preparation of CuCrO2 thin films and coatings, such as reactive sputtering deposition, 37,38 pulsed laser deposition, 39,40,41,42 chemical solution deposition, 43,44,45,46 and molecular beam epitaxy. 47 However, these techniques may not be vital for the depositions where a precise thickness control (of the order of sub-nanometer) over a large-area and/or nanostructured substrate is required. 48,49 Atomic layer deposition (ALD) 50 is an advanced thin-film technique that affords precise film-thickness control owing to its unique deposition mechanism based on sequential and repeated exposure of precursor vapors that undergo self-limiting surface reactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, particularly in the case of CuCrO 2 , valence band changes have been reported in crystalline thin films due to surface preparation [12]. As our Cu x CrO y thin films on glass are polycrystalline in nature, they will not have a coherent surface termination unlike in situ cleaved single crystals.…”
Section: A Surface Preparationmentioning
confidence: 99%
“…In addition, the polycrystalline nature of thin films of glass will not have a coherent surface termination as in situ cleaved films, leading to the loss of fine structure in our measurements. It has been previously reported that the surface termination can significantly alter the valence-band shape in CuCrO 2 [12].…”
Section: Valence-band Compositionmentioning
confidence: 99%
See 1 more Smart Citation